Pengaruh Harga, Promosi Dan Kualitas Produk Terhadap Loyalitas Konsumen Pada Pengguna Smartphone Xiaomi Di Kecamatan Garum Kabupaten Blitar - Dimas Bavi Romadhon; Siti Asiyah; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract   This study aims to determine the effect of Price, Promotion and Product Quality on Consumer Loyalty on Xiaomi smartphone users in Garum District, Blitar Regency. The population used in this study is an unknown number of Xiaomi smartphone users. The sample consists of 107 samples of respondents. The method of data collection in this study used the distribution of questionnaires. The analytical method used is multiple linear regression analysis and processing using SPSS 22. The results of this study simultaneously show that Price, Promotion and Product Quality have a positive and simultaneous effect on Consumer Loyalty. Partially, Price and Promotion have no effect on Consumer Loyalty, while Product Quality has a significant effect on Consumer Loyalty. Keywords: Price, Promotion, Product Quality, Consumer Loyalty.